SILURIAN SEDIMENTATION IN EAST SIBERIA: EVIDENCE FOR VARIATIONS IN THE RATE OF TECTONIC SUBSIDENCE OCCURRING WITHOUT ANY SIGNIFICANT SEA-LEVEL CHANGES - Artyushkov E.V.; Chekhovich P.A. (My University, 2003)
It is widely accepted that major variations of sea-level have occurred in the Phanerozoic. Third-order cycles, 1–10 Ma long with amplitudes of 20–100 m, are of special interest for geochronology and petroleum geology. The amplitude of sea-level changes in the Silurian was estimated based on highly detailed data on the East Siberian Basin, which was 2×106 km2 in size. Fischer plots were compiled based on the thickness of 54 chronostratigraphic units — chronozones, each corresponding to a time interval c.0.5 Ma long. The synchronicity of the chronozones ensures reliable comparison of the changes occurring with time in accommodation space in different regions. The subhorizontal Fischer plots derived for several regions indicate that sea-level changes were very small in the Silurian (<-5–10 m). A mathematical analysis of relative sea-level changes, which takes into account the finite rate of crustal subsidence and different possible forms of eustatic fluctuation, shows that from the observed structure of numerous Silurian successions in East Siberia, eustatic third-order sealevel changes could not have exceeded 6–20 m. In several regions of East Siberia, the rate of crustal subsidence varied as much as several hundred per cent at different times. These variations showed good similarity in form, but their amplitudes were different at different places in the basin. Most probably they were caused by variations in the rate of phase transformations in mafic rocks in the lower crust. Based on the example of the East Baltic, the absence of large-scale third-order cycles in eustatic changes of sea-level has been proven earlier for the Cambrian and earliest Ordovician. Probably, a similar situation was characteristic of many other epochs, when no large glaciations occurred, while many rapid changes of water depth in cratonic areas actually resulted from vertical crustal movements.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская